Farmers’ Perceptions Of The Cultivation Of Porang Frog Seeds in Cilimus Village, Teluk Pandan District, Pesawaran - Alfarisy, M. Ali Fikri; Trully Gultom, Dame; Silviyanti, Serly; K. Rangga, Kordiyana (Politeknik Negeri Lampung, 2023)
Porang (Amorphophallus muelleri), often known as iles-iles, is a plant that contains carbohydrates, fats, proteins, minerals, vitamins, and dietary fibre. The purpose of the study was to determine farmers' perceptions of the cultivation of porang frog seeds and the factors related to farmers' perceptions of the cultivation of porang frog seeds. The research was conducted in Cilimus Village, Teluk Pandan District, Pesawaran Regency. Data collection was carried out in March–April 2022. The respondents were 35 porang farmers, who were taken from all populations. Data collection was carried out using the census method. The data analysis methods used were descriptive analysis and Spearman Rank Correlation. The results showed that there was a respondent's perception that the production and farming of porang frog seeds were quite in line with market demand and local community habits. To get a good profit (financially) in the process of farming the porang frog seeds, it requires a long time and high costs. Porang frog seeds are not difficult to cultivate, quite easy to plant in any field, and the rules are easy to understand. Cultivating porang frog seeds is easier than other plants; it is easy to prepare tools and materials, and it is not difficult to find buyers. Trials and training on the cultivation of porang frog seeds have been carried out but have not fully received support from the government. The cultivation of porang frog seeds is easy to observe, and it is not difficult to get information about porang plants. Factors related to farmers' perceptions of the cultivation of porang frog seeds are social environment, motivation, and knowledge. The suggestion is to increase farmers' knowledge about porang plants so that other farmers are also interested in doing porang farming so that they can increase perception, production, and income, which of course also requires an important role from the related government in providing support by providing seeds for trials or training and PPL as a companion.